Statistical trend analysis of physically unclonable functions : an approach via text mining /: an approach via text mining. (2021) - Zolfaghari, Behrouz; Bibak, Khodakhast; Koshiba, Takeshi; Nemati, Hamid R, 1958-; (Computer scientist), Mitra, Pinaki
No abstract available